Method for preparing modified copper current collector and lithium-sulfur battery

CN116845251BActive Publication Date: 2026-10-09INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311015775.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2026-10-09
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

[0004]为此,本发明所要解决的技术问题在于提供一种改性铜集流体的制备方法和锂硫电池,以解决现有铜箔沉积锂均匀性差等原因导致的锂硫电池电化学性能差的问题

Benefits of technology

[0025] 1. This invention prepares a modified copper current collector, NMMF-Cu, by loading MgF2 and Na3MnF6 onto copper foil in a one-step process. The NMMF-Cu current collector reduces the nucleation overpotential of Li, and the presence of the lithiophilic layers Na3MnF6 and MgF2 promotes uniform nucleation and deposition of lithium ions, thereby suppressing lithium dendrite growth. The Li|NMMF-Cu half-cell using NMMF-Cu as the current collector exhibits a high and stable coulombic efficiency (98.7%) over 100 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116845251B_ABST
    Figure CN116845251B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of modified copper current collector and a lithium-sulfur battery. The preparation method comprises the following steps: step A, soaking copper foil in dilute hydrochloric acid, and then washing the copper foil with anhydrous ethanol and deionized water alternately until the washing liquid is neutral, and drying the copper foil for standby; step B, stirring and uniformly mixing magnesium chloride and potassium permanganate solution in water to obtain a mixed solution A; step C, adding sodium fluoride solution into the mixed solution A and stirring to obtain a mixed solution B; and step D, immersing the copper foil into the mixed solution B, taking out the copper foil after the immersion, washing the copper foil with anhydrous ethanol and deionized water alternately, and drying the copper foil to obtain the modified copper current collector. Depositing lithium on the prepared modified copper current collector to obtain an NMMF-Cu foil, and using the NMMF-Cu foil as a negative electrode of the lithium-sulfur battery can effectively improve the cycle stability of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-sulfur battery technology. Specifically, it relates to a method for preparing modified copper current collectors and lithium-sulfur batteries. Background Technology

[0002] Copper foil is an indispensable basic material due to its high safety, lightweight nature, relative stability in air, and good conductivity. Therefore, it is used as the negative electrode current collector in lithium-ion and lithium metal batteries, and the current collector is a crucial component of lithium metal batteries. The working principle of a lithium metal battery is to convert chemical energy into electrical energy, and the copper foil is the medium for transmitting the generated electrical energy. Lithium dendrites are the most serious problem in lithium metal negative electrodes. Inducing lithium metal to grow towards dendrite-free growth can effectively mitigate the "shuttle effect" and improve battery cycle stability. Although the surfaces of copper foil and lithium sheets appear smooth, they still have many unevennesses. Modifying the current collector to change its surface morphology and make lithium metal deposition more uniform and stable is very important.

[0003] The energy density of lithium metal batteries is limited by issues such as lithium dendrites and poor conductivity of the cathode, preventing them from reaching their full potential. The rough surface of commercial copper foil leads to uneven lithium deposition; therefore, optimizing the copper foil surface structure to guide uniform lithium deposition is crucial for battery cycle stability. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to provide a method for preparing modified copper current collector and a lithium-sulfur battery, so as to solve the problem of poor electrochemical performance of lithium-sulfur batteries caused by poor uniformity of lithium deposition on copper foil.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0006] The preparation method of modified copper current collector includes the following steps:

[0007] Step A: Soak the copper foil in dilute hydrochloric acid, then wash it alternately with anhydrous ethanol and deionized water until the washing solution is neutral, and dry it for later use.

[0008] Step B: Mix magnesium chloride and potassium permanganate solution in water until homogeneous to obtain mixed solution A;

[0009] Step C: Add sodium fluoride solution to mixed solution A and stir to mix well to obtain mixed solution B;

[0010] Step D: Immerse the copper foil in mixed solution B. After immersion, remove it and wash it alternately with anhydrous ethanol and deionized water. Then dry it to obtain the modified copper current collector.

[0011] In the above-mentioned method for preparing modified copper current collector, in step B, the molar ratio of magnesium chloride to potassium permanganate is (4-4.5):1, and the initial concentration of magnesium chloride in mixed solution A is 0.6-0.8 mol / L.

[0012] In the above-mentioned method for preparing modified copper current collector, in step C, the concentration of sodium fluoride solution is 0.2-0.3 mol / L; the volume ratio of mixed solution A to sodium fluoride solution is 1:10-12.

[0013] In the above-mentioned method for preparing modified copper current collectors, step D involves soaking for 12–16 hours, drying at 60–70°C, and drying for 10–15 hours.

[0014] In the above-mentioned method for preparing modified copper current collector, in step A, the concentration of dilute hydrochloric acid is 0.5-1 mol / L, and the soaking time is 3-10 min.

[0015] In the above-mentioned method for preparing modified copper current collector, in step A, the concentration of dilute hydrochloric acid is 1 mol / L and the soaking time is 3 min. If the concentration of hydrochloric acid is too low or the soaking time is too short, it will not effectively remove impurities from the surface of the copper foil. However, if the concentration of hydrochloric acid is too high or the soaking time is too long, it will damage the surface of the copper foil.

[0016] In step B, the molar ratio of magnesium chloride to potassium permanganate is 4:1, and the initial concentration of magnesium chloride in mixed solution A is 0.64 mol / L.

[0017] In step C, the concentration of the sodium fluoride solution is 0.22 mol / L; the volume ratio of mixed solution A to sodium fluoride solution is 1:10; lithium fluoride, formed by the combination of fluoride ions and lithium ions, is a component of the solid electrolyte interphase (SEI) membrane, enabling the SEI membrane to have a fast lithium ion transport rate and regulating the uniform deposition of lithium metal. Therefore, fluoride ions play a major role. If the sodium fluoride content in the system is too high, it will affect the loading of other ions; if its content is too low, it will affect the function of fluoride ions.

[0018] In step D, the soaking time is 12 hours, the drying temperature is 60°C, and the drying time is 12 hours. If the drying temperature is too low or the drying time is too short, liquid will remain on the surface of the copper foil, affecting the battery performance. If the drying temperature is too high or the drying time is too long, it will affect the performance of the copper foil.

[0019] A lithium-sulfur battery is prepared by depositing lithium on a modified copper current collector prepared using the above-mentioned method to obtain an NMMF-Cu foil, which is then used as the negative electrode of the lithium-sulfur battery.

[0020] The aforementioned lithium-sulfur battery uses a sulfur / nitrogen-doped iron carbide composite material as the active material of the positive electrode; lithium nitrate is added to the electrolyte.

[0021] The preparation method of the sulfur / nitrogen-doped iron carbide composite material for the above-mentioned lithium-sulfur battery is as follows:

[0022] Sodium ferrocyanide decahydrate was dried at 150℃ for 24 hours to remove water of crystallization, and then heat-treated under a nitrogen atmosphere. The heat treatment conditions were: heating from room temperature to 900℃ at a heating rate of 5℃ / min and holding for 3 hours. The heat-treated product Fe3C@NC material and sulfur were mixed and ground at a mass ratio of 1:1.5 and then subjected to a second heat treatment under an argon atmosphere. After the second heat treatment, sulfur / nitrogen-doped iron carbide composite material was obtained. The conditions for the second heat treatment were: first, the mixture of sulfur and Fe3C@NC material was placed in a tube furnace, then heated to 155℃ at a heating rate of 5℃ / min and held at 155℃ for 12 hours.

[0023] The electrolyte of the aforementioned lithium-sulfur battery is composed of lithium nitrate, lithium bis(trifluoromethanesulfonyl)imide, ethylene glycol dimethyl ether, and 1,3-dioxane; the concentration of lithium bis(trifluoromethanesulfonyl)imide in the electrolyte is 1 mol / L, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxane is 1:1, and the mass fraction of lithium nitrate is 4 wt%.

[0024] The technical solution of the present invention achieves the following beneficial technical effects:

[0025] 1. This invention prepares a modified copper current collector, NMMF-Cu, by loading MgF2 and Na3MnF6 onto copper foil in a one-step process. The NMMF-Cu current collector reduces the nucleation overpotential of Li, and the presence of the lithiophilic layers Na3MnF6 and MgF2 promotes uniform nucleation and deposition of lithium ions, thereby suppressing lithium dendrite growth. The Li|NMMF-Cu half-cell using NMMF-Cu as the current collector exhibits a high and stable coulombic efficiency (98.7%) over 100 cycles.

[0026] 2. The NMMF-Cu current collector with deposited lithium was used as the negative electrode of the Li-S battery, and the S / Fe3C@NC electrode was used as the positive electrode of the lithium-sulfur battery. The electrolyte with 4% lithium nitrate was used as the electrolyte of the lithium-sulfur battery. Under the conditions of N / P ratio of 1:1 and low electrolyte volume (20μL), the NMMF-Cu current collector enabled the S / Fe3C@NC positive electrode to achieve an initial discharge capacity of 510mAh / g, and the capacity retention rate was 79.6% after 80 stable cycles. Attached Figure Description

[0027] Figure 1a Actual photograph of the bare copper surface in an embodiment of the present invention;

[0028] Figure 1b Actual photograph of the NMMF-Cu copper surface in an embodiment of the present invention;

[0029] Figure 1c SEM image (10 μm) of bare copper surface in an embodiment of the present invention;

[0030] Figure 1d SEM image (10 μm) of NMMF-Cu copper surface in an embodiment of the present invention;

[0031] Figure 1e SEM image (5 μm) of NMMF-Cu copper surface in an embodiment of the present invention;

[0032] Figure 2 XRD patterns of bare Cu and NMMF-Cu in the embodiments of the present invention;

[0033] Figure 3a Na elemental mapping spectrum on the surface of NMMF-Cu in this embodiment of the invention;

[0034] Figure 3b F element mapping spectrum of NMMF-Cu surface in the embodiments of the present invention;

[0035] Figure 3c Mg elemental mapping spectrum on the surface of NMMF-Cu in this embodiment of the invention;

[0036] Figure 3d Mn elemental mapping spectrum on the NMMF-Cu surface in this embodiment of the invention;

[0037] Figure 4a Photographs of lithium deposition on bare copper surfaces in embodiments of the present invention;

[0038] Figure 4b Photographs of lithium deposition on the NMMF-Cu surface in embodiments of the present invention;

[0039] Figure 4c Another photograph of lithium deposition on the NMMF-Cu surface in this embodiment of the invention;

[0040] Figure 5a SEM image (20 μm) of lithium deposition on a bare copper surface in an embodiment of the present invention;

[0041] Figure 5b SEM image (10 μm) of lithium deposition on a bare copper surface in an embodiment of the present invention;

[0042] Figure 5c SEM image (5 μm) of lithium deposition on a bare copper surface in an embodiment of the present invention;

[0043] Figure 5d SEM image (20 μm) of lithium deposited on the NMMF-Cu surface in this embodiment of the invention;

[0044] Figure 5eSEM image (10 μm) of lithium deposited on the NMMF-Cu surface in this embodiment of the invention;

[0045] Figure 5f SEM image (5 μm) of lithium deposited on the NMMF-Cu surface in this embodiment of the invention;

[0046] Figure 6 In the embodiments of the present invention, bare Cu and NMMF-Cu are at 0.5 mA / cm 2 -1 mAh / cm 2 The first charge-discharge curve is shown below;

[0047] Figure 7 In the embodiments of the present invention, bare Cu and NMMF-Cu are at 0.5 mA / cm 2 -1 mAh / cm 2 Half-cell coulomb efficiency diagram;

[0048] Figure 8a In this embodiment of the invention, the Li|NMMF-Cu half-cell operates at 0.5 mA / cm². 2 and 1mAh / cm 2 Voltage distribution diagram below;

[0049] Figure 8b EIS diagrams of Li|Cu and Li|NMMF-Cu half-cells after 1 and 50 cycles in embodiments of the present invention;

[0050] Figure 9 XRD pattern of NMMF-Cu after the first cycle in this embodiment of the invention;

[0051] Figure 10a XPS full spectrum of NMMF-Cu after the first cycle in this embodiment of the invention;

[0052] Figure 10b N1s spectrum of NMMF-Cu after the first cycle in this embodiment of the invention;

[0053] Figure 10c F1s spectrum of bare copper after the first cycle in this embodiment of the invention;

[0054] Figure 10d The F1s spectrum of NMMF-Cu after the first cycle in this embodiment of the invention;

[0055] Figure 11a Cycling performance curves of Li / Cu|S / Fe3C@NC and Li / NMMF-Cu|S / Fe3C@NC batteries at 0.1 A / g in embodiments of the present invention;

[0056] Figure 11bCharge-discharge curves of the Li / NMMF-Cu|S / Fe3C@NC battery in this embodiment of the invention. Detailed Implementation

[0057] 1. Preparation of modified copper current collector NMMF-Cu

[0058] Cut a square copper foil. First, immerse the copper foil in 1 mol / L dilute hydrochloric acid for 3 minutes, then wash it alternately with ethanol and deionized water until the surface of the copper foil is cleaned of dilute hydrochloric acid. Dry the foil for later use. Mix 0.61 g MgCl2, 0.25 g KMnO4, and 10 mL deionized water and stir until homogeneous. Mix 0.91 g NaF with 100 mL deionized water and stir until homogeneous. Combine the two solutions and immerse the prepared copper foil in the mixture for 12 hours. Remove the foil and wash it alternately with ethanol and deionized water until the surface of the copper foil is cleaned of the mixed solution. Then, dry the foil in a constant temperature drying oven at 60°C for 12 hours. The prepared modified copper current collector is denoted as NMMF-Cu.

[0059] 2. Surface morphology and structural characterization of modified copper current collector NMMF-Cu

[0060] Figure 1a and Figure 1b Macroscopic images of commercial copper foil and NMMF-Cu foil are shown. Commercial copper foil is as follows... Figure 1a The bright orange NMMF-Cu foil shown is as follows Figure 1b The two colors, a deep brown, show a significant difference. The morphological changes of the copper foil before and after modification were observed using SEM, such as... Figures 1c to 1e As shown in the image. Figure 1c The SEM image of the surface of commercial copper foil shows that it is rough and uneven. During lithium deposition, it is easy to cause uneven lithium deposition, which in turn leads to irregular lithium dendrites, which puncture the separator and aggravate the shuttle effect of polysulfides between the positive and negative electrodes. Figure 1d and Figure 1e The image shows a SEM image of the NMMF-Cu surface, which reveals a layer of blocky and spherical material evenly distributed on the copper foil surface. This enhances the adhesion of the copper foil to lithium and inhibits the growth of lithium dendrites.

[0061] like Figure 2The XRD patterns of bare copper and NMMF-Cu are shown. It can be seen that NMMF-Cu exhibits three characteristic peaks at 2θ = 43.18°, 2θ = 50.32°, and 2θ = 74°, which completely coincide with the characteristic peaks of bare copper, indicating that the modification of NMMF-Cu is caused within the copper foil and is unrelated to external factors. NMMF-Cu exhibits two characteristic peaks at 2θ = 36.28° and 2θ = 61.2°, corresponding to the (-121) and (311) crystal planes. MgF2 and Na3MnF6 were successfully grown on the surface of the modified copper foil, indicating the success of the copper foil modification. During the initial discharge process, Na... + Mg 2+ and Mn 2+ The lithium metal will be reduced in situ and deposited on the substrate surface to induce uniform nucleation of lithium metal and avoid lithium dendrite growth.

[0062] Figures 3a to 3d The EDS images showed a uniform distribution of four elements—sodium (Na), manganese (Mn), magnesium (Mg), and fluorine (F)—on the surface of the copper foil. This indicates that a dense and uniform protective layer was formed on the surface of the modified copper foil, which improved the stability of the copper foil, facilitated the uniform deposition of lithium ions, and effectively suppressed the growth of lithium dendrites.

[0063] To investigate the deposition behavior of lithium on bare copper and NMMF-Cu surfaces, Li-Cu half-cells were assembled using bare copper and NMMF-Cu as current collectors and lithium metal sheets as anodes, respectively. The deposition morphologies of lithium on the two different current collectors were compared. The deposition morphology of lithium metal determines the reversibility of the lithium deposition / stripping process and affects the tendency for internal short circuits in the battery, thus determining the battery's safety. First, at 0.5 mA cm⁻¹... -2 At a current density, a 1 mAh cm⁻¹ Li-Cu half-cell deposited in the form of discharge. -2 Lithium metal was deposited onto two types of current collectors, and after cycling, the deposition morphology of lithium on the two current collectors was observed by in-situ scanning electron microscopy. Figure 4a This is a macroscopic photograph of lithium deposition on a bare copper surface. The macroscopic photograph shows that the lithium metal deposited on the bare copper surface is uneven and cracks appear in the middle and at the edges. Figures 4b to 4c These are macroscopic images of lithium deposition on the surface of NMMF-Cu current collectors. Compared to bare copper, the lithium deposited on the surface of NMMF-Cu current collectors is relatively dense and uniform, with no obvious cracks. The macroscopic images correspond to scanning electron microscope images of lithium deposition on the surfaces of the two current collectors.

[0064] To further observe the surface morphology evolution of lithium metal deposited on bare copper current collectors and NMMF-Cu current collectors, SEM tests were performed. Figures 5a to 5cThe SEM image of lithium deposited on the bare copper surface shows that, due to the rough and uneven surface of the bare copper current collector, the lithium metal deposited on the bare copper surface exhibits agglomeration and an uneven morphology in terms of deposition thickness. This may lead to the growth of lithium dendrites and the formation of dead lithium, resulting in the loss of active lithium metal. Figures 5d to 5e The SEM image shows the lithium deposition morphology on the NMMF-Cu surface. It clearly shows a uniform distribution of lithium metal on the NMMF-Cu current collector surface. A magnified view reveals a dense lithium metal deposition without voids, demonstrating that the modified copper foil can prevent lithium dendrite growth, thus improving battery performance and lifespan. This is mainly attributed to the large surface morphology and flatter plane of NMMF-Cu, which provides a lithiophilic layer and more lithium nucleation sites.

[0065] In lithium metal batteries, lithium deposition is typically caused by heterogeneous nucleation on the substrate. The initial nucleation mechanism of lithium metal has a significant impact on its growth morphology, and is key to suppressing undesirable morphologies (needle-like, moss-like, dendritic) growth. According to classical nucleation theory, lithium metal nucleation requires overcoming a nucleation energy barrier, and this barrier is closely related to the nucleation overpotential. Generally, the nucleation overpotential is the difference between the lowest voltage point and the voltage plateau; it represents the energy required for lithium nucleation, and a lower overpotential value indicates easier nucleation. + Key parameters for deposition. Figure 6 This shows the charge-discharge curves of Li|Cu and Li|NMMF-Cu half-cells during the first charge and discharge cycle. As shown in the figure, at 0.5 mA / cm²... -2 At the given current density, the voltage drops to -0.1163V (vs Li) during the initial deposition of Li on a bare copper current collector. + / Li), then a plateau is formed and gradually stabilizes at -0.0341V (vs Li). + From the equation / Li), it can be calculated that bare copper has a relatively large nucleation overpotential, approximately 82mV; while for the NMMF-Cu current collector, the voltage drops to -0.0620V (vs Li) during the initial stage of Li deposition on its surface. + / Li), then a plateau is formed and gradually stabilizes at -0.0295V (vs Li). + Similarly, the nucleation overpotential of the NMMF-Cu current collector was calculated to be approximately 33 mV, showing a significant decrease. Compared to bare copper current collectors, the reduction in nucleation overpotential during Li deposition on the NMMF-Cu surface is likely due to the fact that NMMF-Cu provides more nucleation sites, lowers the lithium nucleation barrier, regulates uniform lithium metal deposition, and inhibits the formation of dendritic lithium. Furthermore, the lithiophilic nature of the NMMF-Cu current collector surface enhances its binding with lithium, which is more conducive to stable lithium deposition.

[0066] The rough surface of copper current collectors leads to significant lithium loss per cycle, even at shallow depositions (0.5 mA cm⁻¹) at low current densities. -2 1mAh cm -2 Uneven lithium deposition on the copper foil was also observed, leading to poor deposition / stripping reversibility during charge / discharge. To investigate the deposition / stripping reversibility of the Li|NMMF-Cu half-cell, half-cells were assembled using lithium as the negative electrode and Cu and NMMF-Cu as current collectors, respectively. Their coulombic efficiency (CE) was tested in an ether electrolyte (1M LITFSIDOL / DME 4.0% LiNO3). Figure 7 The figure shows the Li|Cu and Li|NMMF-Cu half-cells at 0.5 mA / cm². 2 The electrochemical performance of the two half-cells after 100 cycles at the specified current density is shown in the graph. After 100 cycles, the Li|NMMF-Cu half-cell exhibits a high and stable CE (98.7%), while the half-cell using bare copper as the current collector shows a rapid CE decay after 85 cycles. This rapid capacity decay is likely due to the uneven deposition of lithium metal on the bare copper, resulting in lithium dendrites piercing the SEI film and causing a significant loss of active material. The NMMF-Cu current collector effectively induces uniform lithium metal deposition, thus enabling the half-cell to have a stable CE and a long cycle life.

[0067] Figure 8a The figure shown is at 0.5 mA / cm -2 1mAh cm -2 Under the given conditions, the voltage distribution curves of the Li|NMMF-Cu half-cell under different cycles show that the coulombic efficiency of the half-cell based on the NMMF-Cu current collector is relatively stable, and the voltage distribution curve did not change after 100 cycles. Electrochemical impedance spectroscopy was used to analyze the internal resistance and interfacial stability of the Li|Cu and Li|NMMF-Cu half-cells. Figure 8b The figures show the interfacial resistivity (EIS) of Li|Cu and Li|NMMF-Cu half-cells after 1 and 50 cycles, respectively. After 1 cycle, the interfacial resistivity of the Li|NMMF-Cu half-cell is lower than that of the Li|Cu half-cell. After 50 cycles, the increase in the high-frequency semicircle size indicates an increase in the thickness of the resistive SEI layer in the Li|Cu half-cell. In contrast, the decrease in the high-frequency semicircle size of the NMMF-Cu-based half-cell suggests that the electrode surface remains stable.

[0068] During the first charge and discharge cycle of the battery, the lithium metal at the negative electrode comes into contact with the electrolyte and reacts, forming an interface layer on the lithium metal surface. This interface layer allows lithium ions to pass through but acts as an electronic insulator, and is called the SEI film. The SEI film is mainly composed of inorganic components (LiF, Li2O, LiOH, Li2CO3, etc.) and organic components (ROLi, ROCO2Li, etc.), and many studies have confirmed the existence of the SEI film. A Li-Cu half-cell was assembled using NMMF-Cu as the current collector. After the first charge and discharge cycle, the battery was disassembled, the copper foil was removed, and its surface XRD was measured. The test results are as follows: Figure 9 As shown.

[0069] Figure 9 The XRD pattern of NMMF-Cu after the first cycle is shown. NMMF-Cu exhibits three characteristic peaks at 2θ = 42.98°, 2θ = 50.1°, and 2θ = 74.08°, which completely coincide with the characteristic peaks of bare copper. Compared to the bare copper surface, the NMMF-Cu surface shows a weak diffraction peak at 2θ = 33.04° for LiN3 compounds, and weak diffraction peaks at 2θ = 37.72° and 2θ = 44.98° for LiF compounds. Since LiF and LiN3 are components of the SEI film, this indicates that an SEI film was formed on the lithium metal anode surface after the first charge-discharge cycle.

[0070] To further elucidate the composition of the SEI film, XPS characterization was performed. Figure 10a The image shows the XPS full spectrum of NMMF-Cu after the first cycle of the Li|NMMF-Cu half-cell. The presence of carbon, nitrogen, oxygen, lithium, fluorine, sodium, magnesium and manganese can be seen from the figure. Figure 10b It is an N1s spectrum with two peaks at 399.7 eV and 401.2 eV, corresponding to Li3N and Li2N2O2, respectively. Figure 10c This is the F1s spectrum of the bare copper surface after one cycle. Figure 10d The image shows the F1s spectrum of the NMMF-Cu surface after one cycle. Compared to bare copper, the LiF peak intensity at 685.5 eV in NMMF-Cu is significantly enhanced, further confirming the successful loading of fluorine in NMMF-Cu. The XPS spectra above confirm the presence of LiF and LiN3 compounds, consistent with the XRD results. Li2N2O2 is the reduction product of the electrolyte additive LiNO3. LiF is a key component for maintaining the stability of the SEI film, possibly due to a potential adhesive effect between the two, and the SEI film containing LiF exhibits rapid Li... + Lithium ion transport rate can improve the redox kinetics of the battery. LiNO3 typically decomposes below 1.6V, and the decomposition products LiN3 and Li2N2O2 can effectively promote the lithium ion transport rate and regulate the uniform and stable deposition of lithium metal.

[0071] 3. Application of NMMF-Cu in lithium-sulfur batteries

[0072] The ratio of the actual capacity of lithium anode to sulfur cathode material per unit area is called the N / P ratio. To evaluate the practical application potential of NMMF-Cu foil in lithium metal batteries, under the conditions of N / P ratio of 1:1 and low electrolyte dosage (20 μl), commercial copper foil with deposited lithium and NMMF-Cu foil with deposited lithium were used as anodes and combined with S / Fe3C@NC cathodes. The cycle performance of the two batteries was evaluated at a current density of 0.1 A / g.

[0073] Preparation of S / Fe3C@NC cathode:

[0074] (1) Sodium decahydrate ferrocyanide was dried at 150℃ for 24h to remove the water of crystallization and then heat-treated under a nitrogen atmosphere. The heat treatment conditions were: heating from room temperature to 900℃ at a heating rate of 5℃ / min and holding for 3h; the heat-treated product Fe3C@NC material and sulfur were mixed and ground at a mass ratio of 1:1.5 and then placed under an argon atmosphere for a second heat treatment. After the second heat treatment, sulfur / nitrogen-doped iron carbide composite material was obtained. The conditions for the second heat treatment were: first, the mixture of sulfur and Fe3C@NC material was placed in a tube furnace, then heated to 155℃ at a heating rate of 5℃ / min and held at 155℃ for 12h to obtain S / Fe3C@NC material.

[0075] (2) Weigh appropriate amounts of polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (N-MP) into a weighing bottle and stir until a suitable viscosity is achieved (the viscosity is moderate when the mass fraction of PVDF is 8-10 wt%). Then, mix the S / Fe3C@NC composite material with conductive carbon black and add it to the binder in several batches. Stir with a magnetic stirrer for 12 hours to obtain a uniform slurry. The mass ratio of S / Fe3C@NC composite material, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) is 75:15:10. Using a 100 μm coating applicator, evenly coat the slurry onto aluminum foil that has been wiped clean with alcohol, and place it in a vacuum drying oven to dry at 60°C for 12 hours to obtain the positive electrode sheet for lithium-sulfur batteries. Use a punching machine to punch the dried electrode sheet into S / Fe3C@NC positive electrodes with a diameter of 12 mm.

[0076] The assembly of the electrodes, electrolyte, and battery used in this embodiment was completed in a Microna glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm). For the preparation of the electrolyte with a 1:1 ratio of 1M LITFSI (lithium bis(trifluoromethanesulfonyl)imide), DOL (1,3-dioxapentane), and DME (ethylene glycol dimethyl ether), 0.574 g of LITFSI was weighed, and 1 ml of DME was added and stirred until the LITFSI powder was completely dissolved. Then, 1 ml of DOL was added and stirred until homogeneous. Based on this, 4.0 wt% LiNO3 was added and stirred for 12 hours to obtain the electrolyte of this embodiment: 4.0% LiNO3 in DOL / DME (v / v 1:1).

[0077] Battery assembly: Using plastic tweezers, place the negative electrode shell, spring contact, stainless steel gasket, lithium metal negative electrode sheet, electrolyte, separator, electrolyte, positive electrode, stainless steel gasket, and positive electrode shell in the middle in sequence. Seal the assembled battery with a button cell packaging machine, and wipe the electrolyte overflowing from the surface of the positive and negative electrode shells with lint-free paper. Let it stand at room temperature for 12 hours before testing. The button cell model used in this test is the standard CR2032.

[0078] The cycle performance of Li / Cu|S / Fe3C@NC and Li / NMMF-Cu|S / Fe3C@NC batteries at 0.1 A / g is as follows: Figure 11a As shown, the initial discharge capacity of the Li / NMMF-Cu|S / Fe3C@NC battery is 510 mAh g. -1 The discharge capacity of the second cycle was 401 mAh g. -1 After 80 cycles, the battery discharge capacity is 319 mAh g. -1 The capacity retention rate was 79.6%, and the capacity decay rate per cycle was 0.25%. However, the initial discharge capacity of the Li / Cu|S / Fe3C@NC battery was 525 mAh g. -1 The second cycle discharge capacity is 397 mAh g. -1 After 80 cycles, the battery discharge capacity is 242 mAh g. -1 The capacity retention rate decreased to 61.0%, and the capacity decay rate per cycle was 0.49%. Figure 11b The figure shows the charge-discharge voltage curves of the Li / NMMF-Cu|S / Fe3C@NC battery. As can be seen from the figure, the voltage curve of the battery is very stable within 80 cycles, which further proves that NMMF-Cu can effectively ensure the uniform deposition and stripping of lithium metal and avoid the growth of lithium dendrites.

[0079] 4. Conclusion

[0080] This embodiment employs a simple one-step method to load MgF2 and Na3MnF6 onto the surface of commercial copper foil, naming it NMMF-Cu. The surface morphology and composition of NMMF-Cu were analyzed using SEM, XRD, and XPS. The performance of the Li|NMMF-Cu battery was tested using a blue electric shock testing system and EIS. Compared to commercial copper foil, the effect of NMMF-Cu on lithium metal deposition was investigated, and its application in Li-S batteries was examined; the main conclusions are as follows:

[0081] (1) The copper current collector was modified with NaF, MgCl2, and KMnO4. SEM, EDS, and XRD confirmed the successful loading of lithiophilic substances MgF2 and Na3MnF6 onto the copper current collector. Macroscopic and microscopic images of lithium deposition on bare copper and the modified copper current collector NMMF-Cu showed that the lithium deposited on the NMMF-Cu current collector surface was more dense and uniform. Furthermore, the NMMF-Cu current collector reduced the nucleation overpotential of Li, regulated uniform lithium metal nucleation, and promoted Li... + Uniform deposition suppresses lithium dendrite growth, improving battery performance and lifespan. Blue electrode testing shows that the modified NMMF-Cu current collector exhibits a high and stable CE (98.7%) in lithium copper half-cells compared to commercial copper foil, and can cycle stably for 100 cycles. EIS testing shows that the interface resistance of the Li|NMMF-Cu half-cell after 50 cycles is lower than that of the Li|Cu half-cell, demonstrating the stability of the electrode surface in the NMMF-Cu-based half-cell. XRD and XPS analysis confirms the presence of inorganic substances such as LiF and LiN3 in the SEI film on the lithium metal surface after charge-discharge of the NMMF-Cu-based half-cell. SEI films containing these inorganic phases exhibit rapid Li... + The transmission rate can accelerate the reaction kinetics of the battery.

[0082] (2) When NMMF-Cu current collector is applied to Li-S battery, under the conditions of N / P ratio of 1:1 and low electrolyte amount (20μl), NMMF-Cu current collector enables the initial discharge capacity of S / Fe3C@NC cathode to reach 510mAh / g, and the capacity retention rate is 79.6% after 80 stable cycles.

Claims

1. A method for preparing modified copper current collectors, characterized in that, Includes the following steps: Step A: Soak the copper foil in dilute hydrochloric acid, then wash it alternately with anhydrous ethanol and deionized water until the washing solution is neutral, and dry it for later use. Step B: Stir and mix magnesium chloride and potassium permanganate solution in water until homogeneous to obtain mixed solution A; the molar ratio of magnesium chloride to potassium permanganate is (4-4.5):1, and the initial concentration of magnesium chloride in mixed solution A is 0.6-0.8 mol / L; Step C: Add sodium fluoride solution to mixed solution A and stir to obtain mixed solution B; the concentration of sodium fluoride solution is 0.2-0.3 mol / L; the volume ratio of mixed solution A to sodium fluoride solution is 1:10-12. Step D: Immerse the copper foil in mixed solution B. After immersion, remove it and wash it alternately with anhydrous ethanol and deionized water. Then dry it to obtain the modified copper current collector. The immersion time is 12-16 hours, the drying temperature is 60-70℃, and the drying time is 10-15 hours.

2. The method for preparing the modified copper current collector according to claim 1, characterized in that, In step A, the concentration of dilute hydrochloric acid is 0.5–1 mol / L, and the soaking time is 3–10 min.

3. The method for preparing the modified copper current collector according to claim 1, characterized in that, In step A, the concentration of dilute hydrochloric acid is 1 mol / L, and the soaking time is 3 min; In step B, the molar ratio of magnesium chloride to potassium permanganate is 4:1, and the initial concentration of magnesium chloride in mixed solution A is 0.64 mol / L. In step C, the concentration of the sodium fluoride solution is 0.22 mol / L; the volume ratio of mixed solution A to sodium fluoride solution is 1:

10. In step D, the soaking time is 12 hours, the drying temperature is 60℃, and the drying time is 12 hours.

4. A lithium-sulfur battery, characterized in that, Lithium is deposited on the modified copper current collector prepared by the method described in any one of claims 1-3 to obtain an NMMF-Cu foil, which is then used as the negative electrode of a lithium-sulfur battery.

5. The lithium-sulfur battery according to claim 4, characterized in that, Sulfur / nitrogen-doped iron carbide composite material is used as the active material for the positive electrode of lithium-sulfur batteries; Lithium nitrate is added to the electrolyte.

6. The lithium-sulfur battery according to claim 5, characterized in that, The preparation method of sulfur / nitrogen-doped iron carbide composite material is as follows: Sodium ferrocyanide decahydrate was dried at 150℃ for 24 hours to remove water of crystallization, and then heat-treated under a nitrogen atmosphere. The heat treatment conditions were: heating from room temperature to 900℃ at a heating rate of 5℃ / min and holding for 3 hours. The heat-treated product Fe3C@NC material and sulfur were mixed and ground at a mass ratio of 1:1.5 and then subjected to a second heat treatment under an argon atmosphere. After the second heat treatment, sulfur / nitrogen-doped iron carbide composite material was obtained. The conditions for the second heat treatment were: first, the mixture of sulfur and Fe3C@NC material was placed in a tube furnace, then heated to 155℃ at a heating rate of 5℃ / min and held at 155℃ for 12 hours.

7. The lithium-sulfur battery according to claim 6, characterized in that, The electrolyte is composed of lithium nitrate, lithium bis(trifluoromethanesulfonyl)imide, ethylene glycol dimethyl ether and 1,3-dioxane; in the electrolyte, the concentration of lithium bis(trifluoromethanesulfonyl)imide is 1 mol / L, the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxane is 1:1, and the mass fraction of lithium nitrate is 4 wt%.